IMPLEMENTASI NILAI-NILAI PENDIDIKAN AGAMA ISLAM DALAM MEMAKMURKAN MASJID DARUL HIKMAH PIMPINAN CABANG MUHAMMADIYAH PONOROGO JL. HOS COKROAMINOTO PONOROGO - Zainur Rizqi, Jeffi; Syarifan Nurjan; Muh. Tajab (LPPM STAI Muhammadiyah Probolinggo, 2023)
The problem raised in this study is the implementation of Islamic Education values ​​and the extent of the success of the Takmir in prospering the mosque, as well as knowing the supporting factors and obstacles to efforts to prosper the Darul Hikmah Mosque. The purpose of this study is to determine the implementation of Islamic education values ​​at the Darul Hikmah Mosque in Ponorogo. This research is a qualitative descriptive study. The types of data used in this study are primary and secondary data. The research instruments are several people related to this research then developed with observation, interview and documentation check guidelines. While the data processing and data analysis techniques through three stages: data reduction, data presentation and conclusion drawing. The results of this study indicate that the implementation of Islamic education values ​​at the Darul Hikmah Mosque through activity programs carried out by Takmir and congregation, namely: Values ​​of faith, morals, worship, cleanliness, social care, history, aqidah, ihsan, da'wah, character, patience, steadfastness, discipline, and togetherness. Therefore, to realize the vision and mission of the Darul Hikmah Mosque, the mosque management must continue to innovate in order to create a model mosque, especially in Ponorogo Regency. However, along the way, there are several supporting factors that need to be maintained and developed, as well as inhibiting factors that must be addressed